EVALUATING A MULTIMEDIA-AIDED AI-INTEGRATED APPROACH TO ENHANCE ENGAGEMENT AND LEARNING OUTCOMES IN SHAANXI ART EDUCATION - Shi , Fengrui; Chee , Ken Nee; Wang, Yongling (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2026)
The rapid advancements in artificial intelligence will bring further changes within the field of educational technology in terms of how effectively students learn, the amount of hands-on experience gained, and the breadth of disciplines integrated into the learning experience. Art educators in Shaanxi province, China face the challenge of educational technology's potential generational gap, the distance and access divide, the time costs of teaching methods, and the pedagogy of art educators. Incorporating artificial intelligence in art education is of course an educational technology change that is taking place. This is a unique way of assessing the impact of a multimedia-assisted, artificial intelligence integrated approach in art education on the level of engagement and learning outcomes of students at the higher education level in Shaanxi, China. The research focused on 50 undergraduate (control group=25, experimental group=25) art students from Shaanxi. While the control group received traditional instruction using only PowerPoint presentations, the experimental group utilized a multimedia-assisted approach integrated with artificial intelligence. The peer collaboration of the students was measured at five intervals over the course of the semester using the LMS and a Likert scale survey wherein students rated peer collaboration. The use of multimedia and artificial intelligence (AI) also increased learning engagement in students. Specifically, students in the experimental group spent 14.88 more minutes learning than students in the control group. The experimental group had 13 more discussion contributors. Additionally, the experimental group had less distractibility (6.84 points less) and test anxiety (7.53 points less) than the control group. Overall, learning outcomes, as evidenced by creative projects, critical thinking, and collaboration, were also more positive in the experimental group, as were retention and overall academic performance. Therefore, the multimedia approach integrated with AI is highly effective in improving engagement and learning outcomes in art education in Shaanxi.